Gravitationally lensed quasars in Gaia – II. Discovery of 24 lensed quasars. Issue 4 (14th April 2018) - Lemon, Cameron A; Auger, Matthew W; McMahon, Richard G; Ostrovski, Fernanda
ABSTRACT: We report the discovery, spectroscopic confirmation, and preliminary characterization of 24 gravitationally lensed quasars identified using Gaia observations. Candidates were selected in the Pan-STARRS footprint with quasar-like WISE colours or as photometric quasars from Sloan Digital Sky Survey (SDSS), requiring either multiple detections in Gaia or a single Gaia detection near a morphological galaxy. The Pan-STARRS grizY images were modelled for the most promising candidates and 60 candidate systems were followed up with the William Herschel Telescope. 13 of the lenses were discovered as Gaia multiples and 10 as single Gaia detections near galaxies. We also discover 1 lens identified through a quasar emission line in an SDSS galaxy spectrum. The lenses have median image separation 2.13 arcsec and the source redshifts range from 1.06 to 3.36. 4 systems are quadruply imaged and 20 are doubly imaged. Deep CFHT data reveal an Einstein ring in one double system. We also report 12 quasar pairs, 10 of which have components at the same redshift and require further follow-up to rule out the lensing hypothesis. We compare the properties of these lenses and other known lenses recovered by our search method to a complete sample of simulated lenses to show the lenses we are missing are mainly those with small separations and higher source redshifts. The initial Gaia data release only catalogues all images of ∼30 per cent of known bright lensed quasars, however the improved completeness of Gaia data release 2 will help find all bright lensed quasars on the sky.